The Influence of Macroeconomic Factors on Government Debt Policy for the 1990-2022 Period - Didi Takwijudin; Taosige Wau (STKIP Taman Siswa Bima, 2025)
This research aims to determine the influence of macroeconomic factors, such a tax ratio, public spending and Gross Domestic Product (GDP) on government debt policy in Indonesia. The data analysis method used is time series data for the period 1990-2022 with annual data using the Error Correction Model (ECM) approach. This research uses a quantitative analysis method with the Eviewes 9 as analysis tool. Based on the results of the overall test of independent variables, it was found that in the short term there are two variables that have a positive influence on debt policy, namely public spending and GDP. Meanwhile, the tax ratio variable has a negative influence on debt policy. This is caused by a low tax absorption ratio resulting in a budget deficit which will increase the debt ratio. However, based on test results using a long-term approach, it was found that all independent variables had a negative influence. So, to reduce the high debt ratio, the government must increase the growth of infrastructure and economic development by paying attention to sources of financing other than debt and paying attention to the direction of debt policy.